Violation of collagen metabolism in the development of renal scarring in patients with chronic pyelonephritis = Нарушение обмена коллагена при развитии нефросклероза у больных хроническим пиелонефритом - S. B. Pavlov; W. Zukow (Kazimierz Wielki University, 2016)
Pavlov S. B., Zukow W. Violation of collagen metabolism in the development of renal scarring in patients with chronic pyelonephritis = Нарушение обмена коллагена при развитии нефросклероза у больных хроническим пиелонефритом. Journal of Education, Health and Sport. 2016;6(6):263-278. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55365 http://ojs.ukw.edu.pl/index.php/johs/article/view/3575   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016.   UDC 616.61-002.3-07: 616,633,747 УДК 616.61-002.3-07:616.633.747   Violation of collagen metabolism in the development of renal scarring in patients with chronic pyelonephritis Нарушение обмена коллагена при развитии нефросклероза у больных хроническим пиелонефритом   С. Б. Павлов, В. Жуков S. B. Pavlov, W. Zukow   Харьковская медицинская академия последипломного образования, Харьков, Украина Kharkiv Medical Academy of Postgraduate Education, Kharkiv, Ukraine UMK, Toruń, Poland UMK, Toruń, Poland     Summary Introduction: The main mechanism for the development of chronic renal failure (CRF) is nephrosclerosis - the replacement of the kidney structures connective tissue. The more active the process of sclerosis, the faster irreversible consequences in the form of CKD. Therefore, the actual problem is the evaluation of the connective tissue (CT) reaction as the main mechanism of the pathological process of kidney sclerosis and above all the activity of collagen metabolism like nephrosclerosis marker. Purpose: Identify collagen metabolism disturbances in patients with pyelonephritis, and development of a noninvasive method of research that characterizes the reaction of the connective tissue of a kidney. Materials and methods: For the biochemical characteristics of the metabolism of the CT used for determining the amount of collagen hydroxyproline (OP). Oxiprolinuria daily was studied in groups of patients with chronic pyelonephritis (CP) at various stages of the pathological process. 1 group - patients with CP without manifestations of chronic renal failure, 2 group - patients with CP with the presence of pronounced manifestations of chronic renal failure The results: There was a significant increase in daily excretion of OP in the urine of patients in both groups, most pronounced in patients with chronic renal failure. level selection OP urine - patients in group 1 42,4 ± 4,1 mg / day (p <0.01)in patients in group 2 66,0 ± 8,7 mg / day (p <0.01) at rate of 25,1 ± 0,72 mg / day. The average value of the level of OP patients in Group 1 higher than the average rate of 1.7 times, and the patients in group 2 - 2.6 times has been established that at the heart of sclerotic process is a violation of the dynamic equilibrium between production and the collapse of collagen, resulting in an increase in our daily oxsiprolinuria examinees. Interconnection activity sclerotic process in the kidneys and the content of OP in the urine of patients with CP can be used to develop methods adequate pathogenetic therapy on biochemical basis of monitoring.   Keywords: hydroxyproline, connective tissue, chronic renal failuremost.     Реферат Введение: Основным механизмом развития хронической почечной недостаточности (ХПН) является нефросклероз - замещение структур почки соединительной тканью. Чем активнее процесс склерозирования, тем быстрее наступают необратимые последствия в виде развития ХПН. Поэтому актуальной проблемой является оценка реакции соединительной ткани (СТ) как основного механизма  патологического процесса склерозирования почки и прежде всего активности обмена коллагена как маркера нефросклероза. Цель работы: выявление нарушений обмена коллагена у больных пиелонефритом, и разработка неивазивного метода исследования, характеризующего реакцию соединительной ткани почки. Материалы и методы: Для биохимической характеристики метаболизма СТ использовали определение количества коллагена по оксипролину (ОП). Была изучена суточная оксипролинурия в группах больных хроническим пиелонефритом (ХП) на разных стадиях патологического процесса. 1 группа - больные ХП без проявлений ХПН, 2 группа - больные ХП с наличием выраженных проявлений ХПН. Результаты работы: Наблюдалось достоверное повышение уровня суточной экскреции ОП с мочой у больных обеих групп, наиболее выраженное у больных с ХПН. Уровень выделения ОП с мочой составил: - у больных 1-й группы 42,4 ± 4,1 мг/сут (р < 0,01), у больных 2-й группы 66,0 ± 8,7 мг/сут (р < 0,01) при норме 25,1 ± 0,72 мг/сут. При этом среднее значение уровня ОП у больных 1-й группы превышало среднее значение нормы в 1,7 раза, а у больных 2-й группы - в 2,6 раза. Установлено, что в основе склеротического процесса лежит нарушение динамического равновесия между продукцией и распадом коллагена, следствием чего является увеличение суточной оксипролинурии у обследованных нами больных. Взаимосвязь активности склеротического процесса в почках и содержания ОП в моче больных ХП может быть использована для разработки методов адекватной патогенетической терапии на основе биохимического мониторинга.   Ключевые слова: оксипролин, соединительная ткань, хроническая почечная недостаточность.